2021
DOI: 10.21203/rs.3.rs-928380/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of sperm progression in three dimensions using rapid optical imaging and dynamic mechanical modeling

Abstract: We present a multidisciplinary approach for predicting how sperm cells with various morphologies swim in three-dimensions (3D), over time scales of milliseconds to hours at spatial resolutions of less than half a micron. We created the sperm 3D geometry and built a numerical mechanical model using the experimentally acquired dynamic 3D refractive index profiles of sperm cells swimming freely in vitro as imaged by high-resolution optical diffraction tomography. By controlling parameters in the model, such as th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Most of the 3D trajectories of the normal sperm models were close to the fallopian tube walls near the internal longitudinal folds of the mucosal layer. Our findings match the results of previous studies about tracking healthy human sperm cells (Chenoweth, 2005;Su et al, 2012;Dardikman-Yoffe et al, 2020;World Health Organization, 2021;Nassir et al, 2022;Nassir et al, 2023) and sperm cell-to-surface interactions (Guidobaldi et al, 2015;Rode et al, 2019;Zaferani et al, 2021). For all age groups, most of the normal sperm models accumulated in the intramural and isthmus regions due to the small luminal area.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Most of the 3D trajectories of the normal sperm models were close to the fallopian tube walls near the internal longitudinal folds of the mucosal layer. Our findings match the results of previous studies about tracking healthy human sperm cells (Chenoweth, 2005;Su et al, 2012;Dardikman-Yoffe et al, 2020;World Health Organization, 2021;Nassir et al, 2022;Nassir et al, 2023) and sperm cell-to-surface interactions (Guidobaldi et al, 2015;Rode et al, 2019;Zaferani et al, 2021). For all age groups, most of the normal sperm models accumulated in the intramural and isthmus regions due to the small luminal area.…”
Section: Discussionsupporting
confidence: 90%
“…For all ages, we observed that the normal sperm models moved forward inside the fallopian tube with a small lateral displacement. This swimming behavior is equivalent to the swimming pattern of the normal sperm cells reported in previous bio-mechanical, microfluidic, and experimental imaging studies of human sperm cell motility (Chenoweth, 2005;Su et al, 2012;Sartori et al, 2016;Rode et al, 2019;Dardikman-Yoffe et al, 2020;World Health Organization, 2021;Nassir et al, 2022Nassir et al, , 2023. Figure 4 shows that most of the normal sperm models accumulated in the intramural and isthmus regions due to the small luminal area.…”
Section: Outcome Measurementssupporting
confidence: 75%
See 3 more Smart Citations